Grallipeza Rondani (Diptera: Micropezidae: Taeniapterinae) of the Caribbean and North America - Marshall, S. A. (Zootaxa, 2013)
The Caribbean and North American species of the large, otherwise neotropical genus Grallipeza Rondani (Diptera: Mi-cropezidae: Taeniapterinae) are revised and keyed. One species, G. nebulosa (Loew), is endemic to the southeastern Unit-ed States and eighteen species are endemic to single Caribbean islands. Of these, the following nine are described as new: Grallipeza abeja, G. albiterga, G. cliffi, G. grenada, G. marleyi, G. mellea, G. paraplacida, G. perezi and G. turba.